Comparison of high-flow nasal oxygenation and standard low-flow nasal oxygenation during rigid bronchoscopy: a randomized controlled trial - Hye Jin Kim; Chang Young Lee; Kyuho Lee; Namo Kim; Seungyeon Lee; Young Jun Oh (Korean Journal of Anesthesiology)
Background The efficacy of high-flow nasal oxygenation (HFNO) in improving oxygenation is influenced by several factors, and its effectiveness is not always guaranteed. Therefore, we aimed to compare the effects of HFNO and standard low-flow nasal oxygenation during rigid bronchoscopy in the apneic patients. Methods All patients were administered general anesthesia with full muscle relaxation and were randomly assigned to receive either HFNO (HFNO group) or standard low-flow oxygenation (Standard group). The study endpoints included the lowest peripheral oxygen saturation (SpO2), hypoxemia-related surgical interruptions (SpO2 ≤ 94%), and changes in arterial oxygen tension (PaO2) and carbon dioxide tension (PaCO2) during the apnea period for rigid bronchoscopy. Results A total of 53 patients completed the study. No significant differences were found between the HFNO and the Standard groups in the lowest SpO2 levels (median [Q1, Q3]; 99 [98, 100]% vs. 98 [94, 100]%, P = 0.059) and in the increase rate of PaCO2 (mean ± standard deviation [SD]; 1.6 ± 0.7 mmHg/min vs. 2.0 ± 0.8 mmHg/min, P = 0.064). However, the HFNO group had fewer patients with hypoxemia-related surgical interruptions than the Standard group (1 [3.8%] vs. 8 [29.6%], P = 0.024) and exhibited an attenuated decline rate in PaO2 (median [Q1, Q3]: 4.6 [0.0, 7.9] mmHg/min vs. 10.5 [6.4, 12.9] mmHg/min, P = 0.005). Conclusions While HFNO did not enhance the lowest SpO2 levels in comparison with standard low-flow oxygenation, it did reduce hypoxemia-related surgical interruptions with an attenuated decline in PaO2. Therefore, HFNO has considerable clinical efficacy for rigid bronchoscopy.